2017
DOI: 10.1002/lary.26590
|View full text |Cite
|
Sign up to set email alerts
|

Development of cognitive screening test for the severely hearing impaired: Hearing‐impaired MoCA

Abstract: 1b. Laryngoscope, 127:S4-S11, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 25 publications
3
102
0
7
Order By: Relevance
“…The HI‐MoCA contains all of the components of the standard MoCA, but the instructions and test stimuli are presented through a PowerPoint presentation. Participants are provided with response worksheets that correspond with the instructions and tasks presented on the PowerPoint presentation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HI‐MoCA contains all of the components of the standard MoCA, but the instructions and test stimuli are presented through a PowerPoint presentation. Participants are provided with response worksheets that correspond with the instructions and tasks presented on the PowerPoint presentation.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that CI users perform better on certain tests, such as the numbers reversed task, when it is administered in the visual modality rather than the auditory modality . Lin et al created the HI‐MoCA, where all instructions are visually presented through a PowerPoint presentation and participants respond to the test items on worksheets or verbally. Per the protocol by Lin et al, verbal responses are prompted only for the serial subtraction and verbal fluency components, and written responses are obtained for all other HI‐MoCA items (see Table for a full description of the tasks).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the limited consensus on patient presentations that should prompt screening and referral for CI, there was no consensus on the best screening assessment to use. A plethora of research has been conducted on the relationship between CI and HL using a variety of CI screening and diagnostic tools, yet only one study to our knowledge has been conducted to attempt establishment of validation of an instrument designed specifically for patients with HL . Though the audiology literature has suggested that the MoCA may be the best CI screening tool to use for adults with ARHL, mounting evidence points toward the need for development of tools specifically validated for this population .…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports from the audiology and psychiatry literature have reviewed and summarized the two most well‐known and used cognitive screening tests for the general community and the subset of those with HL, the Montreal Cognitive Assessment (MOCA) or the Mini‐Mental Status Exam (MMSE); however, dozens more screening tools have been used in the general population . Additionally, work is being put into the validation of CI screening tools made specifically for patients with ARHL, such as the HI‐MOCA . Still, there have been no published guidelines to assist providers in determining the appropriate clinical setting or presentation of a patient with ARHL that should prompt CI screening.…”
Section: Introductionmentioning
confidence: 99%